2020
DOI: 10.3390/ani10030384
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Endoplasmic Reticulum Stress Are Involved in the Protective Effect of Alpha Lipoic Acid Against Heat Damage in Chicken Testes

Abstract: Heat stress (HS) causes testicular injury, resulting in decreased fertility. Alpha-lipoic acid (ALA) is a well-known antioxidant. The aim of this study was to investigate the protective effects of ALA on HS-induced testicular damage in chickens. Histological changes; biomarkers of oxidative stress, including glutathione peroxidase (GPx), superoxide dismutase (SOD), catalase (CAT), and malondialdehyde (MDA); markers of endoplasmic reticulum (ER) stress, including glucose-regulated protein 78 (GRP78) and CCAAT/e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…The increased activities of catalase and SOD in the serum of broiler chickens fed SK diets show its potential to scavenge free radicals during the stressful condition of high SD. It has been reported that the stressful condition decreases the SOD and catalase production, which in turn increases MDA production [ 26 ]. There is a positive correlation between high MDA concentrations and lipid peroxidation [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increased activities of catalase and SOD in the serum of broiler chickens fed SK diets show its potential to scavenge free radicals during the stressful condition of high SD. It has been reported that the stressful condition decreases the SOD and catalase production, which in turn increases MDA production [ 26 ]. There is a positive correlation between high MDA concentrations and lipid peroxidation [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The activities of catalase and SOD were decreased in the plasma of broiler chicks fed AST0, which showed that the potential of scavenging free radicals was impaired by heat stress without astaxanthin supplementation. It has been known that the production of SOD and catalase compromises during heat stress, which results in increasing MDA and oxidative stress [ 31 ]. High MDA levels have been known as an indicator of lipid peroxidation [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The paraffin sections preparation was performed as previously described [ 42 ]. The tissue samples fixed in 4% paraformaldehyde were rinsed with running water, followed by dehydration in different concentrations of alcohol and soaking in xylene and paraffin, tissues were embedded in liquid paraffin.…”
Section: Methodsmentioning
confidence: 99%
“…The H.E. staining was performed as previously described [ 42 ]. The paraffin sections (5 μm) were deparaffinized in xylene and rehydrated with a graded series of ethanol, washed with water, and then stained with hematoxylin for 10 min.…”
Section: Methodsmentioning
confidence: 99%